Lytic polysaccharide monooxygenases from Myceliophthora thermophila C1 differ in substrate preference and reducing agent specificity. Issue 1 (December 2016) - Frommhagen, Matthias; Koetsier, Martijn; Westphal, Adrie; Visser, Jaap; Hinz, Sandra; Vincken, Jean-Paul; Berkel, Willem; Kabel, Mirjam; Gruppen, Harry
Abstract Background Lytic polysaccharide monooxgygenases (LPMOs) are known to boost the hydrolytic breakdown of lignocellulosic biomass, especially cellulose, due to their oxidative mechanism. For their activity, LPMOs require an electron donor for reducing the divalent copper cofactor. LPMO activities are mainly investigated with ascorbic acid as a reducing agent, but little is known about the effect of plant-derived reducing agents on LPMOs activity. Results Here, we show that three LPMOs from the fungusMyceliophthora thermophila C1, Mt LPMO9A, Mt LPMO9B andMt LPMO9C, differ in their substrate preference, C1-/C4-regioselectivity and reducing agent specificity.Mt LPMO9A generated C1- and C4-oxidized, Mt LPMO9B C1-oxidized andMt LPMO9C C4-oxidized gluco-oligosaccharides from cellulose. The recently publishedMt LPMO9A oxidized, next to cellulose, xylan, β-(1 → 3, 1 → 4)-glucan and xyloglucan. In addition, Mt LPMO9C oxidized, to a minor extent, xyloglucan and β-(1 → 3, 1 → 4)-glucan from oat spelt at the C4 position. In total, 34 reducing agents, mainly plant-derived flavonoids and lignin-building blocks, were studied for their ability to promote LPMO activity. Reducing agents with a 1, 2-benzenediol or 1, 2, 3-benzenetriol moiety gave the highest release of oxidized and non-oxidized gluco-oligosaccharides from cellulose for all threeMt LPMOs. Low activities toward cellulose were observed in the presence of monophenols and sulfur-containing compounds. Conclusions Several of the most powerful LPMO reducing agents of this study serve as lignin building blocks or protective flavonoids in plant biomass. Our findings support the hypothesis that LPMOs do not only vary in their C1-/C4-regioselectivity and substrate specificity, but also in their reducing agent specificity. This work strongly supports the idea that the activity of LPMOs toward lignocellulosic biomass does not only depend on the ability to degrade plant polysaccharides like cellulose, but also on their specificity toward plant-derived reducing agents in situ.